Decision Support System for Inheritance Distribution According to Islamic Law Using the Forward Chaining Method - Mas Nurul Hamidah; Arif Arizal; Andriano Lukas; Rifki Fahrial Zainal; Ani Dijah Rahajoe (JEECS (Journal of Electrical Engineering and Computer Sciences), 2021)
The rapid development of information technology in all aspects of the field in this digital era is very important, such as in the fields of business economics, agriculture, culture and religion. In the religious field, technological advances will make it easier for people to learn and seek information in the religious field, as is the case in the issue of inheritance distribution which so far not all people understand it, and also the limited number of experts in the field of inheritance. Religious science is expected to provide a way to learn about inheritance easily, and with this expert system the community will be facilitated in terms of inheritance distribution problems using the forward chaining method, the system will be tested with a 100% accuracy level value in 10 tests with variables different heirs, from the test results, it is found that the system can be used properly.